Extraction of hell mucilag of Theobroma cacao L. for use in clarification of juices of Saccharum officinarum - Fernández Escobar, Ángel Oliverio (2022)
The vegetable mucilages traditionally used to clarify sugarcane juices come from balsa wood, guácimo and cadillo, although cocoa shells can also be used. The objective was to establish the state of maturity, chopping condition and time of immersion in water of the national cocoa shell to obtain a natural flocculant. The procedure was established by the heuristic method, prior to establishing the experimental design with 3 factors a*b*c of a complete 2n design, being a factor shell of national cocoa (pintón and mature), b factor condition of cutting (thick pieces from 3.5 to 4.5 cm, and fine pieces from 0.3 to 0.6 cm) and, c factor immersion time in water (60 and 80 minutes), and, from the combination of factors, eight treatments with three repetitions were established, giving 24 experimental units. Ethyl alcohol of 60 °GL in 1.4% was used to accelerate the mucilage extraction process, and 100 ppm of sodium metabisulfite as an antioxidant combined with a thermal shock. The dependent variable was viscosity with a threshold of 30 centipoise. The a1b1c1 treatment (mature national cocoa shell, fine pieces of 0.3 to 0.6 cm, 80 minutes of immersion in water) reached the threshold viscosity established as a goal. It’s concluded that the extraction of mucilage from national cocoa shells is feasible for use as an aid in the clarification of sugarcane juices